Main Aspects and Directions of an Increase in the Innovative Activity of Logistics Operators - Dudin, Mihail N.; Voykova, Natalia A.; Frolova, Evgenia E.; Artemieva, Julia A.; Grebennikov, Valeriy V. (International Review of Management and Marketing, 2017)
In this article, the authors have considered some aspects and perspectives that have both direct and indirect impact on the innovation activity of companies and firms that operate in the logistics market. The main tasks that have been solved in this article include the following: a study of trends and dynamics of development of the global logistics market; a review of transformations in external environment defining the need to strengthen the innovative activity of logistics operators; systematization of the areas where the innovative activity of logistic operators may be implemented in the present and in the near future. Keywords: innovations, logistics, material flow, freight traffic, warehousing, safekeeping. JEL Classifications: L10, L62, M13